2018
DOI: 10.37317/pbss-2018-0006
|View full text |Cite
|
Sign up to set email alerts
|

Selection Effects in Rice as Assessed by Genetic Analysis in Segregating Populations

Abstract: Estimation of selection effects on changes of a trait is of vital importance for the success of any plantbreeding program, and helps to select the desirable breeding method. Heritability and genetic advance areimportant selection parameters, and selection success is a reflectance of selection response. To estimate selectioneffects on rice genetic parameters, a research was conducted using 4 different generations (two parents:Neda and Sadri, and two segregating populations: BC1F1 and BC1S1). After development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…Significant positive estimates of heterosis and heterobeltiosis among physiological and agronomic traits and its components in two studied crosses, which revealed the over-dominance plays an important role in inheritance of those traits. These findings were supported by several studies ( Ahmadikhah, 2018 ; Hossain et al, 2021 ; Kamara et al, 2017 ; Tiwari et al, 2019 ), wherein it has also been suggested that these aforementioned crosses could be used to explore the heterotic effects in hybrid rice breeding programs with water deficit conditions ( Concepcion et al, 2015 ; Guimarães, Stone & Silva, 2016 ; Hassan, 2017 ; Hastini et al, 2021 ; Potkile et al, 2018 ). Furthermore, significant heterosis percentages were recorded for these traits in studied crosses, which was corroborated by previous studies ( Gaballah et al, 2021 ; Ouyang, Li & Zhang, 2022 ; Sakran et al, 2022 ).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Significant positive estimates of heterosis and heterobeltiosis among physiological and agronomic traits and its components in two studied crosses, which revealed the over-dominance plays an important role in inheritance of those traits. These findings were supported by several studies ( Ahmadikhah, 2018 ; Hossain et al, 2021 ; Kamara et al, 2017 ; Tiwari et al, 2019 ), wherein it has also been suggested that these aforementioned crosses could be used to explore the heterotic effects in hybrid rice breeding programs with water deficit conditions ( Concepcion et al, 2015 ; Guimarães, Stone & Silva, 2016 ; Hassan, 2017 ; Hastini et al, 2021 ; Potkile et al, 2018 ). Furthermore, significant heterosis percentages were recorded for these traits in studied crosses, which was corroborated by previous studies ( Gaballah et al, 2021 ; Ouyang, Li & Zhang, 2022 ; Sakran et al, 2022 ).…”
Section: Discussionsupporting
confidence: 55%
“…Moreover, ( h ) played a greater role in the inheritance of all traits in the two crosses, except for number of roots/plant and sterility % in (P 1 × P 2 ) under water deficit conditions, and it was greater than ( d ) in the inheritance of among studied traits. The additive gene actions were detected by several studies in plants ( Ahmadikhah, 2018 ; Ganapati et al, 2020 ; Guimarães, Stone & Silva, 2016 ; Kamara et al, 2017 ). However, Kamara et al (2017) , found a link of additive effects in regulating the expression of plant height, number of panicles/plant, number of filled grains/panicle, sterility % and grain yield/plant, while non-additive gene actions were important for the inheritance of 1,000-grain weight.…”
Section: Discussionmentioning
confidence: 92%